2023
DOI: 10.1108/md-11-2022-1495
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the domain of relationship between happiness management in organizations and the environment

Abstract: PurposeOrganizational happiness has received exponential attention in recent years. To offer an over-view for future research gap, this article produces a comprehensive review by combining bibliometric analysis and interviews to key authors in the field. The main objective of this paper is to show the state of research regarding the environment in the management of happiness in organizations: the evolution of scientific activity, current trends in authorship, topics and future setting research agenda.Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…As a result, territories will be able to enjoy innovative and happy ecosystems where the general interest of citizens is cultivated (Ruiz-Rodr ıguez et al, 2023). Fourthly, innovative personalised tourism services can be considered beneficial instruments to satisfy people's general well-being, especially during leisure time (Rando-Cueto et al, 2023). Fifthly, public governments carry out action plans in the tourism industry that contemplate as a roadmap that organisational innovation and the happiness of its human capital are guarantors of economic and social success (Ravina-Ripoll et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, territories will be able to enjoy innovative and happy ecosystems where the general interest of citizens is cultivated (Ruiz-Rodr ıguez et al, 2023). Fourthly, innovative personalised tourism services can be considered beneficial instruments to satisfy people's general well-being, especially during leisure time (Rando-Cueto et al, 2023). Fifthly, public governments carry out action plans in the tourism industry that contemplate as a roadmap that organisational innovation and the happiness of its human capital are guarantors of economic and social success (Ravina-Ripoll et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Rando-Cueto et al . (2024) provide a comprehensive review of organizational happiness, combining bibliometric analysis and interviews with key authors in the field.…”
Section: Synopsis Of the Special Issue Contributionsmentioning
confidence: 99%
“…A cluster analysis is performed on the keywords of top 500 papers, as shown in Fig. 1a, where a deeper yellow color indicates a higher frequency of the keyword 20 . It is found that the most popular keywords include LMDI model, water consumption, high-quality development, and water resources capacity.…”
Section: Introductionmentioning
confidence: 99%